2017
DOI: 10.1590/s1517-707620170002.0156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and microstructure of high performance concrete containing stabilized nano-silica

Abstract: Nanotechnology can significantly improve the mechanical strength and durability of concrete. At the nanoscale, good dispersion of constituent materials is an essential factor for the improvement of concrete properties. In this scenario, the objective of this research was to evaluate the mechanical properties of high performance concrete containing stabilized nano-silica. The incorporation of nano-silica to the polycarboxylate chemical admixture allowed its application in concrete, since the nano-silica was eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…They used a nano-silica content of 0.25% by weight of cement-based materials. Other researchers such as Braz de Abreu et al [22] reported the use of stabilized nano-silica particles (between 3 and 200 nm in size) in Brazilian-type CP V ARI PLUS Portland cement. They fabricated three types of concrete mixes: a reference concrete, a concrete added with stabilized nano-silica and a concrete including stabilized nano-silica with silica fume.…”
Section: Nanomaterials In Cement-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used a nano-silica content of 0.25% by weight of cement-based materials. Other researchers such as Braz de Abreu et al [22] reported the use of stabilized nano-silica particles (between 3 and 200 nm in size) in Brazilian-type CP V ARI PLUS Portland cement. They fabricated three types of concrete mixes: a reference concrete, a concrete added with stabilized nano-silica and a concrete including stabilized nano-silica with silica fume.…”
Section: Nanomaterials In Cement-based Materialsmentioning
confidence: 99%
“…For this, nanomaterials can be mixed with cementitious matrices to obtain concrete with high mechanical strength [1,2,3,4,5,6,7,8,9,10]. Nanotechnology can facilitate the development of nanomaterials incorporated into cement-based materials to increase their mechanical strength [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25], decreasing their environment impact [26]. The CO 2 emissions generated during the production of ordinary Portland cement can represent approximately between 5% and 7% of the world man-made emissions of this gas [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing nano-silicas in suspension and powdered forms, with similar particle size distributions, Quercia, Lazaro, Geus and Browers (2013) related a higher compressive strength for concretes formulated with the suspension of nano-silica. For nano-silica stabilized in polycarboxylate dispersant, Abreu et al (2017) revealed a gain on the compressive strength, when compared with the reference concrete without nano-silica. Haruehansapong, Pulgern and Chucheepsakul (2014) evaluated the effect of particle size for nano-silica with different specific surface areas.…”
Section: Introductionmentioning
confidence: 93%
“…NS reacts with lime (CH) during cement hydration and generates the production of hydrated calcium silicates (C–S–H) phase, improving the mechanical strength and durability of concrete [ 13 , 14 , 15 ]. Reduction of silica particles size to the nanoscale can significantly affect the cement hydration leading to substantial improvement of strength and compaction of cement matrix microstructure [ 16 , 17 , 18 ]. The studies described in [ 19 , 20 ] have confirmed that the superficial activity of NS in the presence of cement and water is significantly higher than that of SF and Portland cement itself.…”
Section: Introductionmentioning
confidence: 99%